2021
DOI: 10.26858/eralingua.v5i1.14069
|View full text |Cite
|
Sign up to set email alerts
|

Slang Words in Me, and Earl, and The Dying Girl Novel: Type and Interpretation

Abstract: Abstract. As a written representation of society, novel contains sociolinguistic issues which deserve a comprehensive analysis one of which is the use of slang words. This study explored slang words used in Me and Earl and the Dying Girl, a novel written by Jesse Andrews. The aims of this study were to categorize types of slang words used in the novel and to explain the interpretations of them. The data were collected from the dialogues in the novel. Using qualitative approach, the writer used the theory of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…After they conducting the research, they found five types of word formation process, there were clipping process, multiple process, acronym process, coinage process and blending process. The fifth study was written by Nasution, Karimah, Sitepu, Tryana, and Kusumoriny (2021), analysed the slang word found in the novel. In their research concern to the types of slang words used the theory by Chapman (1998).…”
Section: Introductionmentioning
confidence: 99%
“…After they conducting the research, they found five types of word formation process, there were clipping process, multiple process, acronym process, coinage process and blending process. The fifth study was written by Nasution, Karimah, Sitepu, Tryana, and Kusumoriny (2021), analysed the slang word found in the novel. In their research concern to the types of slang words used the theory by Chapman (1998).…”
Section: Introductionmentioning
confidence: 99%